Analysis of Labor Force Participation Rate (TPAK) in Nusa Tenggara Barat Province, Indonesia - Riska Ayu Hidayati; Emi Salmah; Endang Astuti (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
This study aims to analyze Education, Working Age Population, and Economic Growth on Labor Force Participation Rate (TPAK) in Nusa Tenggara Barat Province, from 2012 to 2021. This research uses quantitative methods. The type of data used is secondary data. Data sources were obtained from the Nusa Tenggara Barat Central Bureau of Statistics, and the Central Bureau of Statistics of 10 districts / cities in Nusa Tenggara Barat. The research location is in Nusa Tenggara Barat Province (NTB), while the research object is 10 districts / cities in NTB, The data analysis used is Panel Data Regression analysis. The results showed that: (1), partially the education variable has a negative and significant effect on the labor force participation rate. (2), partially the Working Age Population variable has a positive and significant relationship to the Labor Force Participation Rate in Nusa Tenggara Barat. (3), Partially, Economic Growth has a positive and insignificant effect on the labor force participation rate in the Regency / City of Nusa Tenggara Barat Province. (4), Simultaneously, the variables of Average Years of Schooling, Working Age Population, and Economic Growth together have a significant effect on the labor force participation rate of districts/cities in Nusa Tenggara Barat Province.